Glycopattern comparison of sperm and exosomes from conventional in vitro fertilization and rescue intracytoplasmic sperm injection: Enhancing sperm motility through exosome‐mediated glycan modulation - Muhammad Anas Ramzan; Zhedong Yang; Li Cao; Jinyuan Zhang; Fei Wu; Miaomiao Xin; Bo Guo; Lumin Wang; Lingyu Zhao; Yannan Qin; Chengcheng Liu (View)
Abstract Infertility is a global issue, with male factors contributing to approximately 50% of cases. While assisted reproductive technologies (ART) resolve 30%–50% of cases, 2%–5% of IVF failures require rescue intracytoplasmic sperm injection (RICSI). Sperm glycocalyx is critical for capacitation and fertilization, and sperm‐derived exosomes, essential for cell communication, remain underexplored. This study used lectin microarrays and fluorescence lectin histochemistry to analyze glycopatterns in sperm and exosomes from IVF and RICSI groups, and assessed RICSI sperm motility and glycan expression after exposure to IVF‐derived exosomes. Clinical data from 2023 at Northwest Women and Children's Hospital, China, showed that RICSI couples had longer infertility durations, and younger ages, required lower gonadotropin doses, and retrieved more oocytes, despite lower sperm quality. However, pregnancy rates were similar between RICSI and IVF groups. Glycopattern analysis revealed that αGalNAc, Tn antigen, and GalNAcα1‐3(Fucα1‐2)Gal (DBA‐recognized) glycans were downregulated in RICSI sperm, while Galβ1‐3GalNAcα‐Ser/Thr (T), GalNAcα‐Ser/Thr (Tn), and sialyl‐T (Jacalin‐recognized) were upregulated in RICSI exosomes compared to IVF. Exosomes showed higher expression of PHA‐L‐, SBA‐, and UEA‐I‐bound glycans, but lower AAL‐bound glycans than sperm. DBA is primarily bound to the neck, acrosomal region, plasma membrane, and tail of IVF sperm, but its binding was significantly reduced in RICSI sperm. Functionally, IVF exosomes enhanced RICSI sperm motility in a dose‐dependent manner by upregulating DBA‐recognized glycans. These findings provide insights into biomarkers, IVF optimization, and glycosylation's role in sperm and exosome‐related infertility, suggesting exosome‐based therapy for improving RICSI sperm motility.